TINDAK PIDANA PEMALSUAN SURAT - Ray Cita; Arifai; Kamaruddin (Halu Oleo University, 2024)
Handling criminal acts of letter forgery requires a comprehensive approach through prevention policies, law enforcement, rehabilitation and collaboration between related institutions. Prevention through education, strict supervision, and strengthening document security systems is important to reduce opportunities for counterfeiting. Firm and fair law enforcement provides justice to victims and a deterrent effect for perpetrators. Rehabilitation gives perpetrators the opportunity to change and make positive contributions again. Collaboration between institutions maximizes the effectiveness of treatment, from exchanging information to developing prevention programs. Only with an integrated approach can we tackle mail fraud and protect society.